Strengthening Children’s Religious And Moral Values In Shamil And Dodo Cartoon Film - Septianti, Fitria; Hafidz, Nur (Jurnal Pendidikan Anak, 2021)
The current era of education for children is experiencing a moral crisis in the aspects of religious and moral development. Religious and moral values ​​of children will be formed through interaction and environmental responses to an active five-sensory performance system. Cartoon films are a strategy for developing children's creativity. By presenting imaginative, interactive, and fun story events through the behavior and attitudes of the characters in cartoon films. The cartoon film Syamil and Dodo became a cartoon film by NCR Production which was made to educate children because it was rich in Islamic educational values ​​and religious and moral values ​​which were suitable to stimulate early childhood. The problem in this research is: "How is the strengthening of religious and moral values ​​in the cartoon film Syamil and Dodo?". The research analyzes the strengthening of religious and moral values ​​in the cartoon film Syamil and Dodo. This type of research is library or Library Research using the cartoon film Syamil and Dodo as the primary data source in this study. Meanwhile, secondary data were obtained from journals, books, and previous thesis. The data collection technique in this research is documentation by observing footage from the cartoon film Syamil and Dodo. Based on the research conducted by the author, the cartoon film Syamil and Dodo is a cartoon film suitable for watching early childhood, the film contains religious and moral educational values ​​for children aged 4-6 years. Strengthening the Syamil and Dodo cartoons can be a medium to reflect and actualize how to properly instill religious and moral values ​​for children in the scope of family and school education.